Corrosion prevention method for polar region ice-based material doped with steel fibers

By depositing manganese nickel-based crystal films by hydrothermal method on the surface of steel fibers, the shortcomings of the existing anti-corrosion treatment methods are solved, the corrosion resistance and mechanical properties of steel fibers are improved, and the needs of large-scale engineering applications are met.

CN119843262AActive Publication Date: 2025-04-18INST OF ENG PROTECTION NAT DEFENSE ENG RES INST ACAD OF MILITARY SCI CHINESE PEOPLES LIBERATION ARMY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510331572.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-18
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

The existing steel fiber surface anti-corrosion treatment methods have the disadvantages of easy sedimentation, thin coating, uneven film, and poor durability, which are difficult to meet the needs of large-scale engineering applications.

Method used

The reaction was carried out in a closed reactor by using the hydrothermal method. By chemically depositing a wear-resistant and corrosion-resistant manganese-nickel-based crystal film on the surface of the steel fibers, the corrosion resistance of the steel fibers was improved, and a rough conversion film was formed on the surface to enhance the bonding strength between the steel fibers and the substrate.

Benefits of technology

The corrosion resistance and mechanical properties of steel fibers are improved, and the crystal film formed seals the contact between the steel fibers and the external medium, prevents the chemical and electrochemical reactions of metals, and effectively prevents corrosion of steel fiber materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843262A_ABST
    Figure CN119843262A_ABST
Patent Text Reader

Abstract

A corrosion prevention method for a polar ice-based material doped with steel fibers belongs to the technical field of corrosion prevention of steel fibers for ice-based materials, and comprises the following steps: deoiling, pickling and washing steel fibers, immersing the steel fibers in a film-forming solution composed of water, phosphoric acid, nitric acid, nickel nitrate, sodium molybdate, nickel carbonate and manganese carbonate, placing the film-forming solution in a hydrothermal kettle for surface oxidation treatment, and drying the film-forming solution to obtain the polar ice-based material doped with the steel fibers. The anti-corrosion steel fiber for the polar region ice-based material is prepared. The method has the beneficial effects that a hydrothermal method is utilized, a layer of wear-resistant and corrosion-resistant manganese-nickel-based crystal film is chemically deposited on the surface of the steel fiber, the corrosion resistance of the steel fiber is improved, meanwhile, the surface roughness of a conversion film formed on the surface of the steel fiber is large, the bonding strength of the steel fiber and a matrix is improved, and the mechanical property of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of steel fiber anti-corrosion, and specifically relates to a method for anti-corrosion of polar ice-based materials by mixing steel fibers. Background Art

[0002] The total area of ​​the North and South Poles exceeds 35 million square kilometers. At present, my country has established its own polar research stations in both the North and South Poles. The exploration and evaluation report points out that the North and South Poles are rich in energy, minerals, biological resources, etc. For example, the Arctic has 13% of the world's unproven oil reserves, 30% of the world's undeveloped natural gas reserves and 9% of the world's coal resources; the minerals contained in the polar regions include gold, copper, iron, lead, platinum, nickel, zinc, etc. In addition, the polar regions have very important strategic significance in the military due to their special geopolitical pattern. Therefore, the development and utilization of the polar regions are increasingly valued by various countries. The polar environment is an extreme environment with special conditions such as low temperature, high seawater salinity, strong wind, high waves, storms, snow, floating ice and polar night. It is significantly different from the traditional marine corrosion environment, and therefore puts forward more stringent requirements on the corrosion of polar materials. Ultra-high performance ice-based materials are a new type of composite materials with ultra-high mechanical properties, high toughness, ultra-high durability and excellent casting and molding properties. The steel fiber mixed in it as a structural material accounts for a large proportion, which can give full play to the characteristics of each component material and the performance transfer between each other, improve the mechanical properties of the ice-based matrix, and have the advantages of good toughness, strong fatigue resistance and wear resistance, and can effectively limit cracks and crack propagation in any direction. The application of steel fiber ice-based materials has obvious advantages, giving full play to the matrix reinforcement advantages of steel fibers. The reliable bonding between steel fibers and ice-based materials is the basic condition for the two to work together, but the corrosion of steel fibers is a factor that affects the durability of components in actual engineering applications. The most prominent problem is the main factors affecting material corrosion in polar regions, including the following four points: first, higher wind speed, and the wind will contain particles that damage the material surface; second, higher solar radiation, leading to aging of organic materials; third, soluble salts in snow and ice on the material surface; fourth, the summer temperature will be higher than the melting point of ice and snow, resulting in the material surface being covered with a soluble salt film. Studies have shown that in the Antarctic area with a high altitude and close to the South Pole, the corrosion of steel materials is relatively mild, at 0.03μm / a. In areas with lower altitudes, the corrosion is relatively severe and fluctuates greatly, at 3.35-36.4μm / a. In areas with slightly lower latitudes in the Arctic, the corrosion is more severe, with the highest corrosion rate reaching 222μm / a. Therefore, the corrosion of materials in polar environments is obvious. In order to prevent durability problems in the structure, the steel fiber can be treated with an anti-corrosion process so that the steel fiber material can still bear force on the components in a corrosive environment, and the supporting structure is safe and stable as a whole. Existing anti-corrosion treatment of steel fiber surface mostly adopts copper plating method. This process has the disadvantages of easy sedimentation, thin coating, uneven film, poor durability, etc., which is difficult to meet the needs of large-scale engineering applications. Based on this, the present invention proposes an anti-corrosion steel fiber for ice-based materials. By using a hydrothermal method, a layer of wear-resistant and corrosion-resistant manganese-nickel-based crystal film is chemically deposited on the surface of the steel fiber to improve the corrosion resistance of the steel fiber. At the same time, the surface roughness of the conversion film formed on the surface of the steel fiber is large, thereby improving the bonding strength between the steel fiber and the matrix, and improving the mechanical properties of the material. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to propose a method for anti-corrosion of polar ice-based materials by adding steel fibers, which is used to solve the shortcomings of the existing anti-corrosion treatment mentioned in the background technology, such as easy sedimentation, thin coating, uneven film, poor durability, etc., which is difficult to meet the needs of large-scale engineering applications.

[0004] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a method for anti-corrosion of polar ice-based materials by adding steel fibers, which comprises degreasing, pickling, and water washing the steel fibers, and then immersing them in a film-forming solution composed of water, phosphoric acid, nitric acid, nickel nitrate, sodium molybdate, nickel carbonate, and manganese carbonate, and placing them in a hydrothermal kettle for surface oxidation treatment to obtain anti-corrosion steel fibers for polar ice-based materials.

[0005] The film-forming solution comprises the following components calculated by weight: 150-200 parts of phosphoric acid, 35-45 parts of nitric acid, 5-10 parts of nickel nitrate, 10-20 parts of sodium molybdate, 1-5 parts of nickel carbonate, 50-70 parts of manganese carbonate and 350-450 parts of water.

[0006] The phosphoric acid used is analytical grade, medium-strength inorganic acid, with a concentration of more than 85%; The nitric acid used is a strong inorganic acid with a commercial concentration of about 68%; The nickel nitrate used was analytical grade, green crystalline powder, with a purity of 99.5%; The sodium molybdate used was analytical grade, white crystals, purity 99%; The nickel carbonate used was analytical grade, light green powder, with a purity of 99.9%; The manganese carbonate used was analytical grade, white micro powder, with a purity of 99.5%.

[0007] The film-forming solution comprises the following components: 150 parts of phosphoric acid, 35 parts of nitric acid, 5 parts of nickel nitrate, 10 parts of sodium molybdate, 1 part of nickel carbonate, 50 parts of manganese carbonate and 350 parts of water.

[0008] The film-forming solution comprises the following components: 200 parts of phosphoric acid, 45 parts of nitric acid, 10 parts of nickel nitrate, 20 parts of sodium molybdate, 5 parts of nickel carbonate, 70 parts of manganese carbonate and 450 parts of water.

[0009] The film-forming solution comprises the following components: 180 parts of phosphoric acid, 40 parts of nitric acid, 8 parts of nickel nitrate, 15 parts of sodium molybdate, 3 parts of nickel carbonate, 60 parts of manganese carbonate and 400 parts of water.

[0010] The film-forming solution comprises the following components: 200 parts of phosphoric acid, 42 parts of nitric acid, 9 parts of nickel nitrate, 18 parts of sodium molybdate, 4 parts of nickel carbonate, 60 parts of manganese carbonate and 420 parts of water.

[0011] A method for anti-corrosion of polar ice-based materials mixed with steel fibers based on the above-mentioned method comprises the following steps: Step 1: Weigh the weight of each component of the film-forming solution, mix water, phosphoric acid and nitric acid and stir them evenly to obtain a mixed solution, and wait for the reaction temperature to drop to room temperature before proceeding to the next step; Step 2: Add nickel nitrate, sodium molybdate and nickel carbonate to the mixed solution obtained in step 1 and stir for 15-20 minutes to fully dissolve them; Step 3: Add manganese carbonate to the mixture in step 2 and stir for about 5 minutes until the solution becomes clear for later use; Step 4: Degreasing the steel fiber, removing the rust on its surface with a 10% hydrochloric acid solution and rinsing it twice with clean water, then placing the steel fiber in a hydrothermal reactor, pouring the clarified solution obtained in step 3 into the steel fiber; Step 5: Place the hydrothermal reactor in an oven at 110°C for 20-30 minutes and then take it out. After the hydrothermal reactor is cooled naturally, the anti-corrosion steel fiber for polar ice-based materials can be taken out.

[0012] The beneficial effects of the present invention are: 1. By using the hydrothermal method to react in a closed reactor, since the hydrothermal reactor has a certain temperature and pressure, the solution and the steel fiber interface react more rapidly, the crystals are easier to crystallize into a film, and the bonding force between the film and the matrix is ​​stronger under a certain pressure, which is more efficient and the film is more compact than the traditional film forming method; 2. The steel fiber surface prepared by the present invention has high film-forming efficiency and large film thickness. Due to the presence of nickel, molybdenum and manganese elements, the formed surface crystal film has roughness, wear resistance and corrosion resistance compared with traditional copper plating and other measures. The crystal film seals the contact between the steel fiber matrix and the external medium, hinders the chemical and electrochemical reactions of the metal, and can effectively prevent the corrosion of the steel fiber material. At the same time, since the crystal film has a certain degree of roughness, it can increase the bonding force between the steel fiber and the ice-based material, thereby improving the mechanical properties and structural stability of the ice-based material. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The scanning electron microscope microscopic morphology of the steel fiber surface after hydrothermal coating in Example 3 of the present invention was viewed 600 times; Figure 2 The scanning electron microscope microscopic morphology of the steel fiber surface after hydrothermal coating in Example 3 of the present invention is 5000 times; Figure 3 The dense film morphology under an optical microscope after 30 days of corrosion on the steel fiber surface after hydrothermal coating in Example 3 of the present invention is 200 times larger; Figure 4 This is the dense film morphology under an optical microscope 500 times after the steel fiber surface is corroded 30 days after hydrothermal coating in Example 3 of the present invention. DETAILED DESCRIPTION

[0014] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0015] The following embodiments are provided in conjunction with the present invention, but the present invention is not limited to the following embodiments: Embodiment 1:

[0016] A method for anti-corrosion of polar ice-based materials by adding steel fibers, wherein the film-forming solution of the steel fibers comprises the following components by weight: 150 parts of phosphoric acid, 35 parts of nitric acid, 5 parts of nickel nitrate, 10 parts of sodium molybdate, 1 part of nickel carbonate, 50 parts of manganese carbonate, and 350 parts of water; The above-mentioned anti-corrosion method of polar ice-based materials mixed with steel fibers comprises the following steps: Step 1: Weigh the weight of each component of the film-forming solution, mix water, phosphoric acid and nitric acid and stir them evenly to obtain a mixed solution, and wait for the reaction temperature to drop to room temperature before proceeding to the next step; Step 2: Add nickel nitrate, sodium molybdate and nickel carbonate to the mixed solution obtained in step 1 and stir for 15-20 minutes to fully dissolve them; Step 3: Add manganese carbonate to the mixture in step 2 and stir for about 5 minutes until the solution becomes clear for later use; Step 4: Degreasing the steel fiber, removing the rust on its surface with a 10% hydrochloric acid solution and rinsing it twice with clean water, then placing the steel fiber in a hydrothermal reactor, pouring the clarified solution obtained in step 3 into the steel fiber; Step 5: Place the hydrothermal reactor in an oven at 110°C for 20-30 minutes and then take it out. After the hydrothermal reactor is cooled naturally, the anti-corrosion steel fiber for polar ice-based materials can be taken out. Embodiment 2:

[0017] A method for anti-corrosion of polar ice-based materials by adding steel fibers, wherein the film-forming solution of the steel fibers comprises the following components by weight: 200 parts of phosphoric acid, 45 parts of nitric acid, 10 parts of nickel nitrate, 20 parts of sodium molybdate, 5 parts of nickel carbonate, 70 parts of manganese carbonate, and 450 parts of water; The above-mentioned anti-corrosion method of polar ice-based materials mixed with steel fibers comprises the following steps: Step 1: Weigh the weight of each component of the film-forming solution, mix water, phosphoric acid and nitric acid and stir them evenly to obtain a mixed solution, and wait for the reaction temperature to drop to room temperature before proceeding to the next step; Step 2: Add nickel nitrate, sodium molybdate and nickel carbonate to the mixed solution obtained in step 1 and stir for 15-20 minutes to fully dissolve them; Step 3: Add manganese carbonate to the mixture in step 2 and stir for about 5 minutes until the solution becomes clear for later use; Step 4: Degreasing the steel fiber, removing the rust on its surface with a 10% hydrochloric acid solution and rinsing it twice with clean water, then placing the steel fiber in a hydrothermal reactor, pouring the clarified solution obtained in step 3 into the steel fiber; Step 5: Place the hydrothermal reactor in an oven at 110°C for 20-30 minutes and then take it out. After the hydrothermal reactor is cooled naturally, the anti-corrosion steel fiber for polar ice-based materials can be taken out. Embodiment 3:

[0018] A method for anti-corrosion of polar ice-based materials by adding steel fibers, wherein the film-forming solution of the steel fibers comprises the following components by weight: 180 parts of phosphoric acid, 40 parts of nitric acid, 8 parts of nickel nitrate, 15 parts of sodium molybdate, 3 parts of nickel carbonate, 60 parts of manganese carbonate, and 400 parts of water; The above-mentioned anti-corrosion method of polar ice-based materials mixed with steel fibers comprises the following steps: Step 1: Weigh the weight of each component of the film-forming solution, mix water, phosphoric acid and nitric acid and stir them evenly to obtain a mixed solution, and wait for the reaction temperature to drop to room temperature before proceeding to the next step; Step 2: Add nickel nitrate, sodium molybdate and nickel carbonate to the mixed solution obtained in step 1 and stir for 15-20 minutes to fully dissolve them; Step 3: Add manganese carbonate to the mixture in step 2 and stir for about 5 minutes until the solution becomes clear for later use; Step 4: Degreasing the steel fiber, removing the rust on its surface with a 10% hydrochloric acid solution and rinsing it twice with clean water, then placing the steel fiber in a hydrothermal reactor, pouring the clarified solution obtained in step 3 into the steel fiber; Step 5: Place the hydrothermal reactor in an oven at 110°C for 20-30 minutes and then take it out. After the hydrothermal reactor is cooled naturally, the anti-corrosion steel fiber for polar ice-based materials can be taken out. Embodiment 4:

[0019] A method for anti-corrosion of polar ice-based materials by adding steel fibers, wherein the film-forming solution of the steel fibers comprises the following components by weight: 200 parts of phosphoric acid, 42 parts of nitric acid, 9 parts of nickel nitrate, 18 parts of sodium molybdate, 4 parts of nickel carbonate, 60 parts of manganese carbonate, and 420 parts of water; The above-mentioned anti-corrosion method of polar ice-based materials mixed with steel fibers comprises the following steps: Step 1: Weigh the weight of each component of the film-forming solution, mix water, phosphoric acid and nitric acid and stir them evenly to obtain a mixed solution, and wait for the reaction temperature to drop to room temperature before proceeding to the next step; Step 2: Add nickel nitrate, sodium molybdate and nickel carbonate to the mixed solution obtained in step 1 and stir for 15-20 minutes to fully dissolve them; Step 3: Add manganese carbonate to the mixture in step 2 and stir for about 5 minutes until the solution becomes clear for later use; Step 4: Degreasing the steel fiber, removing the rust on its surface with a 10% hydrochloric acid solution and rinsing it twice with clean water, then placing the steel fiber in a hydrothermal reactor, pouring the clarified solution obtained in step 3 into the steel fiber; Step 5: Place the hydrothermal reactor in an oven at 110°C for 20-30 minutes and then take it out. After the hydrothermal reactor is cooled naturally, the anti-corrosion steel fiber for polar ice-based materials can be taken out.

[0020] The surface crystal film microstructures formed in the implementation cases are similar, and the test results of Example 3 are used as reference. Figure 1-Figure 4 : Depend on Figure 1 Scanning electron microscope 600 times and Figure 2 Scanning electron microscope 5000 times of the steel fiber surface after hydrothermal coating shows that the crystal film formed on the steel fiber surface is dense and crystalline; Depend on Figure 3 The dense film morphology under an optical microscope after 30 days of corrosion on the steel fiber surface after hydrothermal coating 200 times and Figure 4 The dense film morphology of the steel fiber after hydrothermal coating was observed 500 times under an optical microscope 30 days after corrosion. It was found that the surface of the steel fiber was still compact, dense and uniform after 30 days of corrosion, and the surface was still black, rough, crystalline and without any corrosion holes or rust spots.

[0021] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

[0022] Parts of the present invention not described in detail are prior art.

Claims

1. A method for anti-corrosion of polar ice-based materials by mixing steel fibers, characterized in that: Anti-corrosion steel fibers for polar ice-based materials are obtained by degreasing, pickling, washing, immersing the steel fibers in a film-forming solution consisting of water, phosphoric acid, nitric acid, nickel nitrate, sodium molybdate, nickel carbonate and manganese carbonate, and placing them in a hydrothermal kettle for surface oxidation treatment.

2. The method for anti-corrosion of polar ice-based materials by adding steel fibers according to claim 1 is characterized by: The film-forming solution comprises the following components calculated by weight: 150-200 parts of phosphoric acid, 35-45 parts of nitric acid, 5-10 parts of nickel nitrate, 10-20 parts of sodium molybdate, 1-5 parts of nickel carbonate, 50-70 parts of manganese carbonate and 350-450 parts of water.

3. The anti-corrosion method of polar ice-based materials mixed with steel fibers according to claim 1 is characterized by: The phosphoric acid used in the film-forming solution is analytically pure, medium-strength inorganic acid with a concentration of more than 85%; The nitric acid used is a strong inorganic acid with a concentration of 68%; The nickel nitrate used was analytical grade, green crystalline powder, with a purity of 99.5%; The sodium molybdate used was analytical grade, white crystals, purity 99%; The nickel carbonate used was analytical grade, light green powder, with a purity of 99.9%; The manganese carbonate used was analytical grade, white micro powder, with a purity of 99.5%.

4. The method for anti-corrosion of polar ice-based materials by adding steel fibers according to claim 2, characterized in that: The film-forming solution comprises the following components: 150 parts of phosphoric acid, 35 parts of nitric acid, 5 parts of nickel nitrate, 10 parts of sodium molybdate, 1 part of nickel carbonate, 50 parts of manganese carbonate and 350 parts of water.

5. The method for anti-corrosion of polar ice-based materials by adding steel fibers according to claim 2, characterized in that: The film-forming solution comprises the following components: 200 parts of phosphoric acid, 45 parts of nitric acid, 10 parts of nickel nitrate, 20 parts of sodium molybdate, 5 parts of nickel carbonate, 70 parts of manganese carbonate and 450 parts of water.

6. The method for anti-corrosion of polar ice-based materials by adding steel fibers according to claim 2, characterized in that: The film-forming solution comprises the following components: 180 parts of phosphoric acid, 40 parts of nitric acid, 8 parts of nickel nitrate, 15 parts of sodium molybdate, 3 parts of nickel carbonate, 60 parts of manganese carbonate and 400 parts of water.

7. The method for anti-corrosion of polar ice-based materials by adding steel fibers according to claim 2, characterized in that: The film-forming solution comprises the following components: 200 parts of phosphoric acid, 42 parts of nitric acid, 9 parts of nickel nitrate, 18 parts of sodium molybdate, 4 parts of nickel carbonate, 60 parts of manganese carbonate and 420 parts of water.

8. A method for anti-corrosion of polar ice-based materials by adding steel fibers according to any one of claims 1 to 7, characterized in that: The steps include: Step 1: Weigh the weight of each component of the film-forming solution, mix water, phosphoric acid and nitric acid and stir them evenly to obtain a mixed solution, and wait for the reaction temperature to drop to room temperature before proceeding to the next step; Step 2: Add nickel nitrate, sodium molybdate and nickel carbonate to the mixed solution obtained in step 1 and stir for 15-20 minutes to fully dissolve them; Step 3: Add manganese carbonate to the mixture in step 2 and stir for about 5 minutes until the solution becomes clear for later use; Step 4: Degreasing the steel fiber, removing the rust on its surface with a 10% hydrochloric acid solution and rinsing it twice with clean water, then placing the steel fiber in a hydrothermal reactor, pouring the clarified solution obtained in step 3 into the steel fiber; Step 5: Place the hydrothermal reactor in an oven at 110°C for 20-30 minutes and then take it out. After the hydrothermal reactor is cooled naturally, the anti-corrosion steel fiber for polar ice-based materials can be taken out.

Citation Information

Patent Citations

  • Barrel plating phosphating agent before coating electrophoresis of cartridge case and preparation method thereof

    CN101671823A

  • Phosphating solution for oil casing couplings

    CN103243321A

  • Special anti-corrosion steel fibers for building concrete and preparation method

    CN108358485A

  • Preparation method and application of nickel phosphide flexible fiber supercapacitor electrode

    CN109659155A

  • Phosphating solution, phosphate coating and preparation method and application thereof

    CN111286728A